The British Diplomatic and Political Policy Regarding Balochistan-Punjab Border (Al-Qamar, 2023)
Subcontinent had always been an attractive land for the invaders due its fertility during ancient time and the North western India was major route for this invasion. British advancement started after the victory of the battle of Palsy in 1757 and the forces excelled towards Delhi. British forces occupied Sindh and Punjab. With the annexation of united Punjab British abolished Derajat and they even moved to Baluchistan. With new diplomatic strategy they established peace in the tribal area of the surrounding border of Balochistan. As per Sandeman Policy the tribes of Dera Ghazi Khan were engaged by the British policy and now they were in position to occupy Balochistan and Kalat. It was very important for the British to establish their grip in this area so that may become easy and decrease the pressure of western border from Iran, Afghanistan and Russia. This paper primarily explores the British rule in tribal region of Derajat and Balochistan.
Keywords: Muslims; Rule; Decline; Mughal; Delhi; British; Derajat